Stereoelectronic Characterization and Catalytic Potential of a 1, 3‐Bis(2, 6‐terphenyl)‐Substituted N‐Heterocyclic Carbene. Issue 22 (28th May 2021) - Twycross, Daniel; Davey, Christopher J.; Cole, Marcus L.; McKay, Alasdair I.
Abstract: The preparation of a 1, 3‐bis(2, 6‐terphenyl)imidazol‐2‐ylidene, IDitop (Ditop=2, 6‐bis(4‐tolyl)phenyl‐) is reported. Several late transition metal complexes as well as the selenium adduct of IDitop were prepared to study and compare the stereoelectronic properties of IDitop to other well‐known N‐heterocyclic carbenes (NHCs). A study of the steric character of IDitop taken from crystal structure data of the complexes and adducts reveals a high degree of flexibility. Preliminary application to challenging Suzuki coupling reactions was undertaken. Abstract : A sterically demanding 2, 6‐terphenyl substituted N‐heterocyclic carbene and metal complexes thereof were synthesized. This NHC displays a remarkably flexible steric profile and unique electronic character which is poorly quantified by the models commonly employed.